Electronic measurements and instrumentation - Gnanavadivel, J (Anuradha Publications, 2012)
The significance of this book is to provide a basic knowledge in measurements concepts, basic electronic measurements, signal generators, signal analyzers, digital instruments, data acquisition systems, fiber optic measurements and introduction about virtual instrumention. Each chapter contains solved problems and two mark question and answers to get complete knowledge of the subject.